A clinical introduction to psychosis : foundations for clinical psychologists and neuropsychologists - Badcock, Johanna C.; Paulik, Georgie (Academic Press, an imprint of Elsevier, 2020)
"This practical guide outlines the latest advances in understanding and treating psychotic symptoms and disorders, articulating step-by-step the clinical skills and knowledge required to effectively treat this patient population. A Clinical Introduction to Psychosis takes an evidence-based approach that encourages a wider perspective on clinical practice, with chapters covering stigma and bias, cultural factors, the importance of social functioning, physical health, sleep, and more. A broad array of treatment modalities are discussed, including cognitive behavioral therapy, cognitive remediation, psychosocial interventions, trauma-informed therapies, and recovery-oriented practice. The book also provides a concise overview of the latest advances regarding cognitive profiles in people with psychotic disorders, the developmental progression of cognitive abilities, and the clinical relevance of cognitive dysfunction. The book additionally familiarizes readers with issues and controversies surrounding diagnostic classification, transdiagnostic expression, and dimensional assessment of symptoms in psychosis." -- Publisher's description.